Genomic profiling of metaplastic breast carcinomas reveals genetic heterogeneity and relationship to ductal carcinoma. (November 2018) - Krings, Gregor; Chen, Yunn-Yi
Abstract Metaplastic breast carcinomas comprise a histologically heterogenous group of tumors. Although most are triple (estrogen/progesterone receptor, HER2) negative, these rare tumors are clinicopathologically distinct from other triple negative carcinomas and may be aggressive with worse chemotherapy responses. On the other hand, metaplastic carcinomas are histologically diverse, which is reflected in gene expression differences among subtypes. Whether metaplastic carcinomas are genetically distinct from other triple negative cancers and whether genetic differences underlie histologic subtypes remains poorly understood. We sequenced 408 cancer-related genes in 28 metaplastic carcinomas, including chondroid matrix-producing carcinomas (n = 10), spindle cell carcinomas (n = 5), and carcinomas with squamous (n = 5), mixed spindle/squamous (n = 5), and mixed metaplastic (n = 3) differentiation. Metaplastic carcinomas were highly enriched forPIK3CA /PIK3R1 (61%) and Ras-Map kinase (25%) pathway aberrations compared to other triple negative carcinomas (TCGA dataset 14%, p < 0.001 and 7%, p = 0.005, respectively) and harbored a high frequency ofTP53 (64%) andTERT promoter (25%) mutations, but this varied among subtypes. Chondroid-matrix producing carcinomas lacked PI-3 kinase and Ras-Map kinase aberrations andTERT promoter mutations, compared to 100%, 39%, and 39% of non-matrix-producing tumors, respectively.TERT promoter mutations were enriched (47%) in spindle cell carcinomas and tumors with squamous or spindle/squamous differentiation. Spindle cell carcinomas lackedTP53 mutations, in contrast to other subtypes (78%, p = 0.003). Separate analysis of paired ductal carcinoma in situ and metaplastic carcinoma revealed shared clonality in all cases (n = 8). Activating PI-3 kinase and Ras pathway mutations were early events, and inactivating mutations in tumor suppressors includingRB1, CDKN2A, andTP53 were associated with invasion in individual cases. Metaplastic components of two tumors showed genetic progression from separately sequenced paired invasive ductal carcinoma. The findings suggest that metaplastic carcinomas are genetically distinct from other triple negative breast cancers and highlight genetic heterogeneity that broadly correlates with histologic subtype. Heterologous elements progress from associated ductal carcinoma.